Question about uniqueness of limits...? If f(x)-->L as x-->a and f(x)-->M as x-->a, then prove that L=M for 'f' be a function from R to R. Please tell me its Solution with step by step...! Thanks a lot for this.

Expert Answers

An illustration of the letter 'A' in a speech bubbles

Given `lim_(x->a)f(x)=L,lim_(x->a)f(x)=M` and `f` a function mapping `RR->RR` , Prove L=M.

(1) We assume `L != M` . Let `epsilon = |(L-M)/2|` . Then `|L-M|>epsilon` .

(2) Let `epsilon_1=epsilon/2` .

(3) Since `lim_(x->a)f(x)=L` , there exists `delta_1>0` such that `0<|x-a|<delta_1 => |f(x)-L|<epsilon_1` .

Also `lim_(x->a)f(x)=M` implies there exists `delta_2>0` such that

`0<|x-a|<delta_2 => |f(x)-M|<epsilon_1` .

(4) |L-M|

=|L-f(x)+f(x)-M|        Add and subtract f(x)

`<=` |L-f(x)|+|f(x)-M|     Triangle inequality theorem |a+b|`<=` |a|+|b|

=|f(x)-L|+|f(x)-M|     Property of absolute value |a-b|=|b-a|

(5) Let `delta=min(delta_1,delta_2)`

(6) `0<|x-a|<delta=>|L-M|<epsilon_1+epsilon_1=epsilon/2+epsilon/2=epsilon` . But this contradicts  `|L-M|>epsilon` so L=M. QED.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial Team